Traffic Flow Analysis on Unsignalized T-intersection at Jalan Pekeliling-Jalan Perak 1 at Pasir Gudang Federal Route (FT017), Johor based on Gap Study - Nazaruddin, Muhammad Noor Khairi; Ahmad Termida, Norsitihazlin (Recent Trends in Civil Engineering and Built Environment, 2024)
Unsignalized intersection plays an important role in determining the capacity of road network especially in urban and suburban areas. There are many problems appeared at the intersection such as congestion, queues, delay and accident. The evaluation of capacity at unsignalized intersection is practically measured using the gap acceptance approach and used for unsignalized intersection procedure [1]. This study was conducted at unsignalized T-intersection of Jalan Pekeliling – Jalan Perak 1 at Pasir Gudang Federal Route (FT017) to analyze and evaluate the performance of unsignalized intersection based on gap study. The first objective of this study is to analyze traffic flow parameters at the study location in terms of speed, density and flow. Second objective is to measure a critical gap. The flow and density were measured in every fifteen minutes interval using CountCam2 during morning, afternoon and evening peak hours on a weekday and a weekend, except for speed data that were calculated numerically using Greenshields’ approach. Data of gaps were collected using CountCam2. Raff s method have been used in determination of critical gap. The critical gap for all peak hours were found between 9 seconds to 11 secondsUn